Penyusunan Laporan Keuangan Berdasarkan ISAK 35 dengan Menggunakan Microsoft Excel 2016 pada LKSA Bina Yatim - Annisa Fitriani; Arif Afriady (Indonesian Accounting Literacy Journal, 2021)
Orphanage or LKSA (Institute for Child Social Welfare) is a form of non-profit oriented that earns income from government grants or donations from the public who do not expect compensation for what has been given. LKSA's responsibility for these contributions needs to be transparent and reported regularly in the form of financial statements to avoid misuse of funds and to increase the credibility of LKSA to external parties. Currently, the standard for preparing financial statements that applies to non-profit oriented entities is ISAK 35. However, there are still LKSA that have not implemented this standard. One of them is LKSA Bina Yatim. This study aims to determine how the preparation of financial statements has been carried out, to design financial report formats with Microsoft Excel and compose it based on ISAK 35, and to find out the implications of applying these design and preparation to LKSA Bina Yatim. The research method used descriptive qualitative method. The research data was obtained through interviews, documentation, and literature study. The results of this study indicate that LKSA Bina Yatim is still manual in recording and preparing its financial statements and only prepare a simple income statement that does not follow the standard. Therefore, the authors designed the format for preparing financial statements using Microsoft Excel to assist LKSAs in preparing financial reports based on ISAK 35 in May 2021. The implications of this design and preparation can help LKSA in preparing financial statements effectively and efficiently.